Mothers at the Intersection of Trauma, Addiction, and Involvement with the Criminal Legal System: An Analysis of Multiple Case Studies - Monica Solinas-Saunders PhD; Maureen L. Petrunich-Rutherford PhD; Mark D. Thomas PhD; Natasha R. Brown PhD; Kevin L. McElmurry PhD; Melissa A. Jones PhD; Abigail M. Cognetti BSc; Lytina Andrews BSc; Amira Zahabi BSc (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The study focuses on the complex interconnection of race, sexuality, and socioeconomic background in shaping the stories of mothers struggling with addiction disorders as they attempt to recover from traumatic experiences. A sample of 45 mothers was employed in the study. Using case study analysis methodologies, the stories of 6 mothers were used as representative cases based on their individual characteristics, community settings, and institutional experiences. Further, the 6 cases were used to describe the difficulties experienced by participants across 3 major life transitions: (1) childhood (2) initiation to drug use and addiction disorders (3) motherhood . Across these life transitions, participants emphasized the relevance of traumatic experiences and mental health disorders as main reasons for their drug addiction. For each theme highlighted in the narrative of each case, a connection to all other participants was made to summarize the findings in the whole sample. The analysis indicates that while most mothers experienced trauma during their lifetime, mothers who identified as members of racial/ethnic minorities and those who identified as lesbians were more likely to report trauma from prejudice and discrimination. Furthermore, the analysis highlights that mothers who identified as members of racial minorities were more likely to have their children placed in foster care. In the study, mothers’ involvement with the criminal legal system contributed to the challenges they experienced while renegotiating their relationships with their children. These mothers’ lived experiences and the complexity of the dynamics they described—especially their interactions with the legal system—could potentially help other researchers frame new hypotheses that could be tested by larger empirical studies.